Increases in Arousal are More Long‐Lasting than Decreases in Arousal: On Homeostatic Failures During Emotion Regulation in Infancy. (3rd May 2018) - Wass, Sam V.; Clackson, Kaili; Leong, Vicky
Abstract : In emotion regulation, negative or undesired emotions are downregulated, but there are also opponent processes to emotion regulation—in which undesired emotions are exacerbated dynamically over time by processes that have an amplifying or upregulating impact. Evidence for such processes has been shown in adults, but little previous work has examined whether infants show similar patterns. To examine this, we measured physiological arousal in 57 typical 12 month olds while presenting a 20‐min mixed viewing battery. Fluctuations in autonomic arousal were measured via heart rate, electrodermal activity, and movement. We reasoned that if transitions in autonomic arousal are random (stochastic), then (1) arousal would be normally distributed across the session, and (2) episodes where arousal exceeded a certain threshold above the mean should be as long‐lived as those where arousal exceeded the same threshold below the mean. In fact we found that (1) heart rate and movement (but not electrodermal activity) were positively skewed, and (2) that increases in arousal have a lower extinction probability than decreases in arousal. Our findings may suggest that increases in arousal are self‐sustaining. These patterns are the opposite of the homeostatic mechanisms predicted by naïve approaches to emotion regulation.